Cephalometric evaluation of the effects of the Twin Block appliance in subjects with Class II, Division 1 malocclusion amongst different cervical vertebral maturation stages - Aisha Khoja; Mubassar Fida; Attiya Shaikh
ABSTRACT Objectives: To evaluate the cephalometric changes in skeletal, dentoalveolar and soft tissue variables induced by Clark's Twin Block (CTB) in Class II, Division 1 malocclusion patients and to compare these changes in different cervical vertebral maturation stages. Methods: Pre- and post-treatment/observation lateral cephalograms of 53 Class II, Division 1 malocclusion patients and 60 controls were compared to evaluate skeletal, dentoalveolar and soft tissue changes. Skeletal maturity was assessed according to cervical vertebral maturation stages. Pre- and post-treatment/observation mean changes and differences (T2-T1) were compared by means of Wilcoxon sign rank and Mann-Whitney U-tests, respectively. Intergroup comparisons between different cervical stages were performed by means of Kruskal-Wallis test and Mann-Whitney U-test (p ≤ 0.05) . Results: When compared with controls, there was a significant reduction in ANB angle (p < 0.001), which was due to a change in SNB angle in CS-2 and CS-3 (p < 0.001), and in SNA (p < 0.001) and SNB (p = 0.016) angles in the CS-4 group. There was significant increase in the GoGn-SN angle in CS-2 (p = 0.007) and CS-4 (p = 0.024), and increase in Co-Gn and Go-Gn amongst all cervical stages (p < 0.05). There was significant decrease in U1-SN and increase in IMPA amongst all cervical stages (p < 0.05). There was significant retraction of the upper lip in CS-3 (p = 0.001), protrusion of the lower lip in CS-2 (p = 0.005), increase in nasolabial angle in CS-4 (p = 0.006) and Z-angle in CS-3 (p = 0.016), reduction in H-angle in CS-2 (p = 0.013) and CS-3 (p = 0.002) groups. When pre- and post-treatment mean differences were compared between different cervical stages, significant differences were found for SNA, SNB and UI-SN angles and overjet. . Conclusions: The Twin-Block along with the normal craniofacial growth improves facial esthetics in Class II, Division 1 malocclusion by changes in underlying skeletal and dentoalveolar structures. The favorable mandibular growth occurs during any of the cervical vertebral maturation stages, with more pronounced effect during CS-3 stage.